Validación y aplicación de un ELISA para la cuantificación de anticuerpos IgG contra polisacárido capsular Vi de Salmonella Typhi. - Espinosa-Viñals, Carlos; Soroa-Millán, Yamilka; Martin-García, Yanet; Pérez-Baños, Amarilis; Nicot-Valenciano, Milagros; Rodríguez-Noda, Laura; Gómez-Amador, Aylín; Ramírez-González, Ubel; Soubal-Mora, Jean Pierre; García-Rivera, Dagmar (Revista VacciMonitor (Vacunología y Temas Afines))
An indirect ELISA for the quantification of IgG antibodies against the Vi polysaccharide of this bacteria was developed as a part of the stages of Research and Development of a conjugate vaccinal candidate against Salmonella Typhi. The results of the validation process are presented in this paper, in which the interval and linearity of the curve, the intra- and inter-assay precision, accuracy, specificity, limit of detection and robustness were determined. The calibration curve generated with an internal standard serum provided a good fit to a polynomial function and an interval between 1/100 and 1/3200 dilutions. The coefficients of variation in the precision and robustness tests and the percentages of recovered were in intervals established for each one (≤10%, ≤20% and 90-110%, respectively). The assay presented an optimal specificity, obtaining OD signals above 1.3 for positive sera against Vi and low for sera against unrelated antigens. The results support the use of this quantitative ELISA in immunogenicity assays for batch release of Vi conjugates. Likewise, they support their use for the immunogenicity evaluation of Vi polysaccharide formulations and Vi polysaccharide conjugates to proteins in phases of research and development.